(untitled) (Journal of Basic and Applied Research in Biomedicine, 2023)
Background: The declining trend of male infertility have been attributed to some factors including environmental, lifestyle behaviors, and dietary habits. Bisphenol A (BPA) which is preponderance in the environment and in various products frequently used has been implicated in male infertility. It is not known whether the seminal fluid BPA concentrations differ among men with primary infertility and secondary infertility. This study was aimed at determining the seminal plasma BPA concentrations among men with secondary infertility and primary infertility and to associated their levels with duration of infertility. Materials and Methods: This was a cross‑sectional study of 145 men clinically diagnosed with primary infertility (n=80) and secondary infertility (n=65), and men with proven fertility (n=60) as controls. Semen analysis was done manually according World Health Organization guidelines and seminal plasma BPA was assayed using an Elisa kit. Chi square and Student’s t-test were used to analyze continuous data and discrete variables respectively. Pearson’s correlation coefficient was used to determine the association between seminal plasma BPA and duration of infertility, and a p<0.05 was considered statistically significant. Results: The seminal plasma BPA was significantly higher (p<0.001) among subjects with secondary infertility than those with primary infertility. Sperm count, total motility, progressive motility and normal morphology were lower among secondary infertility than primary infertility, but the mean differences were not significant (p>0.05) except viability which was significantly higher among primary infertility than secondary infertility (p<0.05). The multiple regression model indicates that, the ages of men (OR=3.26 95% CI 2.23-7.26) was independently associated with BPA concentrations among secondary infertility. The finding of higher BPA concentrations in seminal plasma of men with secondary infertility than primary infertility may be associated with age and not duration of marriage.